High-Throughput Cultivation for the Selective Isolation of Acidobacteria From Termite Nests - Oberpaul, Markus; Zumkeller, Celine M.; Culver, Tanja; Spohn, Marius; Mihajlovic, Sanja; Leis, Benedikt; Glaeser, Stefanie P.; Plarre, Rudy; McMahon, Dino P.; Hammann, Peter; Schäberle, Till F.; Glaeser, Jens; et al. (Frontiers in Microbiology, 2020)
Microbial communities in the immediate environment of socialized invertebrates can help to suppress pathogens, in part by synthesizing bioactive natural products. Here we characterized the core microbiomes of three termite species (genus Coptotermes) and their nest material to gain more insight into the diversity of termite-associated bacteria. Sampling a healthy termite colony over time implicated a consolidated and highly stable microbiome, pointing towards the fact that beneficial bacterial phyla play a major role in termite fitness. In contrast, there was a significant shift in the composition of the core microbiome in one nest during a fungal infection, affecting the abundance of well-characterized Streptomyces species (phylum Actinobacteria) as well as less-studied bacterial phyla such as Acidobacteria. High-throughput cultivation in microplates was implemented to isolate and identify these less-studied bacterial phylogenetic group. Amplicon sequencing confirmed that our method maintained the bacterial diversity of the environmental samples, enabling the isolation of novel Acidobacteriaceae and expanding the list of cultivated species to include two strains that may define new species within the genera Terracidiphilus and Acidobacterium.